2019
DOI: 10.3390/ma12213499
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Evaluation on Accuracy of Conventional and Milled Gypsum Models and 3D Printed Photopolymer Models

Abstract: The aim of this study was to evaluate the accuracy of dental models fabricated by conventional, milling, and three-dimensional (3D) printing methods. A reference model with inlay, single crown, and three-unit fixed dental prostheses (FDP) preparations was prepared. Conventional gypsum models (CON) were manufactured from the conventional method. Digital impressions were obtained by intraoral scanner, which were converted into physical models such as milled gypsum models (MIL), stereolithography (SLA), and digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 48 publications
5
69
2
3
Order By: Relevance
“…The controls included were a dental stone cast ( n = 8), a digital STL image of a dental stone cast ( n = 3), typodont digital STL image ( n = 7), typodont ( n = 1), prefabricated resin model digital STL image ( n = 2), patient intraoral scan image (2) or a dry human skull ( n = 1). In addition, there were four studies [ 4 , 35 , 47 , 54 ] that did not include a reference model as a control, rather compared various printing technologies against each other.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The controls included were a dental stone cast ( n = 8), a digital STL image of a dental stone cast ( n = 3), typodont digital STL image ( n = 7), typodont ( n = 1), prefabricated resin model digital STL image ( n = 2), patient intraoral scan image (2) or a dry human skull ( n = 1). In addition, there were four studies [ 4 , 35 , 47 , 54 ] that did not include a reference model as a control, rather compared various printing technologies against each other.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies investigated SLA ( n = 20), MJ ( n = 11), DLP ( n = 9) and, to a lesser extent, FFF ( n = 6), BJ ( n = 2) and CLIP ( n = 1). With regards to printing parameters, one study reported following the manufacturers’ recommendations [ 6 ], while others explicitly detailed the printing parameters used [ 4 , 19 , 36 , 37 , 38 , 42 , 43 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 55 , 56 , 57 ]. In contrast, the remainder of the studies did not provide clear details regarding the printing parameters used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraoral scan data are used for both model manufacturing and restoration design [25]. The working model is manufactured by SM (for example, computer numerical control (CNC) milling) or AM (for example, rapid prototyping).…”
Section: Data Acquisition Processing and Manufacturing In Digital Wmentioning
confidence: 99%